2014
DOI: 10.1016/s1473-3099(14)70811-4
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of a recombinant live attenuated tetravalent dengue vaccine (DENVax) in flavivirus-naive healthy adults in Colombia: a randomised, placebo-controlled, phase 1 study

Abstract: Summary Background Dengue virus is the most serious mosquito-borne viral threat to public health and no vaccines or antiviral therapies are approved for dengue fever. The tetravalent DENVax vaccine contains a molecularly characterised live attenuated dengue serotype-2 virus (DENVax-2) and three recombinant vaccine viruses expressing the prM and E structural genes for serotypes 1, 3, and 4 in the DENVax-2 genetic backbone. We aimed to assess the safety and immunogenicity of tetravalent DENVax formulations. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 48 publications
(60 reference statements)
8
102
1
2
Order By: Relevance
“…Furthermore, a recent Phase I trial of a tetravalent DENV vaccine candidate consisting of an attenuated DENV2 backbone containing prM/E genes of variant serotypes revealed similar problems. While demonstrating acceptable safety, neutralization titers to DENV2 predominated, while DENV4 titers were barely detectable under most inoculation conditions [19]. These results serve as a reminder that chimerization schemes must be carefully considered to preserve viral fitness necessary for induction of balanced immune responses against all four serotypes.…”
Section: Future Perspectivesmentioning
confidence: 86%
“…Furthermore, a recent Phase I trial of a tetravalent DENV vaccine candidate consisting of an attenuated DENV2 backbone containing prM/E genes of variant serotypes revealed similar problems. While demonstrating acceptable safety, neutralization titers to DENV2 predominated, while DENV4 titers were barely detectable under most inoculation conditions [19]. These results serve as a reminder that chimerization schemes must be carefully considered to preserve viral fitness necessary for induction of balanced immune responses against all four serotypes.…”
Section: Future Perspectivesmentioning
confidence: 86%
“…In a randomized controlled phase I study in Philippine, Capeding et al [30] reported that a vaccine regime of either 3 TDV vaccination administered over a year or two TDV vaccination given more than 8 months apart led to a balanced antibody response to all four dengue serotypes among flavivirus-exposed populace that included children [31]. The reactogenicity did not increase with successive vaccination and was not higher in children than in adults and adolescents.…”
Section: Methods Of Data Collectionmentioning
confidence: 99%
“…There is data on safety and immunogenicity for individuals aged up to 45 but there is no efficacy data for individuals above the age of 1636, [37]. Osorio et al [31] reported that there is acceptable tolerability and immunogenicity of the tetravalent DENVAX formulation in healthy, flavivirus-naïve adults but more clinical studies are needed to test DENVAX in different age groups in DENV-endemic areas. Although TDV is safe, a number of adverse events have been reported.…”
Section: Methods Of Data Collectionmentioning
confidence: 99%
“…The results showed that the vaccine was safe, generally well-tolerated, and immunogenic. 90,94 In subjects tested in the USA, the overall seroconversion rates and geometric mean titers at day 120 after two doses of the vaccine were highest for DENV-2 (92.1% and a PRNT 50 of 292.8), followed by DENV-1 and DENV-3 and were lowest for DENV-4 (71.1% and a PRNT 50 titer of 15.0). Further development of this vaccine is needed to induce a more balanced immune response among all four DENV serotypes.…”
Section: Current Status Of Dengue Vaccine Developmentmentioning
confidence: 99%